Do common owners influence corporate social responsibility? Firm-level evidence from China - Suyan Yan (China Journal of Accounting Research, 2021)
Using a sample of Chinese A-share listed companies from 2007 to 2018, this article explores the influence of common owners on corporate social responsibility (CSR). The results show that common owners significantly promote CSR investment, indicating that increased CSR represents a bright side to common owners, in contrast to their anticompetitive effect. Further analysis shows that the nature of state ownership significantly weakens the positive relationship between common owners and CSR investment. Prospector firms strengthen the positive influence of common owners on CSR investment, whereas defender firms weaken the effect. Moreover, common owners benefit from increasing CSR investment, and co-owned firms benefit by easing their financial constraints when they invest or increase their investment in social responsibility. The findings enhance the outstanding of how common owners affect corporate behavior and enrich the literature on common ownership and CSR investment.
Keywords: 650; Common owners; Corporate social responsibility; State-owned enterprises; Corporate strategy; Stock returns; Financial constraints